Struggling for cultural survival: Hungarian identity discourses in the face of assimilation - Andits, Petra (The Australian journal of anthropology, 2017)
The Hungarian immigrant community in Australia is struggling with cultural survival. The diaspora has experienced a general decline in community participation as a result of the aging of the émigré population and the rapid assimilation of subsequent generations. Using data derived from the series of annual community-organised conferences called Megmaradásunk Konferenciák, this article compares the different discourses articulated by community leaders in Australia seeking to preserve and strengthen the diaspora community. I examine how newly emerged narratives of ‘diaspora death’ and cultural survival are debated and how possibilities of strengthened connections with Hungary have impacted these discussions.